Lean Supply Chain Management Practices and Process Innovation for Sustainable Performance and Impact in the Thai Automotive Manufacturing Industry: An Integrate framework - Sutama Thunyachai, Adisak Theeranuphattana, Varattaya Jangkrajarng (International Journal of Advanced Science and Technology, 2020)
Automotive manufacturing companies are now being pressured to operate sustainably by governments and customers. Many companies are using lean supply chain management (LSCM) practices to reduce waste over their organizational value chain, which contributes to sustainable development Innovating process (PI), sustainable development, environmental management systems and eco-design have been also used to satisfy consumers ’ needs and the regulations of policymakers.. This is significant because both lean supply chain management practices and process innovation involve performance. The research first proposes an integrated framework for three structures (lean supply chain management practices, process innovation, and sustainability perform). This conceptual framework is based on LSCM that considers three factors: supplier factors, operations factors, and customer factors. In this model, the following sustainability performance is defined as dependent variables: Economic (EC), Environmental (EN), and Social (SC). Finally, this study offers practitioners a introduce model for the lean supply chain management practices with sustainability performance.